Religião e escola: as condições de escolarização de estudantes evangélicos em uma escola pública de ensino médio - Marcos Antônio Silva (2023)
This thesis aims to know and analyze the schooling conditions of evangelical students in a state high school on the outskirts of Belo Horizonte Metropolitan Region (RMBH), with an increasing number of young pentecostal students. We focused on key dimensions of the teaching-learning process, such as the interpersonal relationships between educators and students, the curriculum, the pedagogical practices, and peer socialization. We opted for a case study encompassing the direct observation of school routine, questionnaires with students and teachers, and interviews with a small group of students. Our findings point out a strong presence of Pentecostal evangelical churches in the school territory and their role in the community in areas like leisure, sport, culture, and social assistance. We highlight the conflicts between students’ religious practice/belonging and the public school, which states to be laic. These conflicts impact the transmission of school knowledge in the classroom, the establishment of youth identity and sociability, and the interaction with peers and educational personnel.